Factors That Influence Muzakki Intention to Pay Zakat at Zakat Institutions - Durratul Haninda Is'ad; Ach. Yasin (EKSYAR : Jurnal Ekonomi Syari'ah & Bisnis Islam (e-Journal), 2023)
The public's interest in paying Zakat is high, as evidenced by the rising Zakat potential and national Zakat collecting performance yearly. However, the zakat collection at L.A.Z. remains suboptimal compared to the zakat collection outside the zakat institution. This study aims to see how Zakat's knowledge, service quality, and brand awareness influence Muzakki's intention to pay Zakat at YDSF Surabaya. This study uses quantitative research methodologies with a sample size of 100 respondents, using multiple linear regression analysis. The results of this study showed that both variables of zakat knowledge and brand awareness partially had a significant impact on the intention to pay Zakat. However, service quality did not significantly impact the intention to pay Zakat. With an R2 of 53.4%, the three variables of zakat knowledge, service quality, and brand awareness simultaneously affected Zakat paying intention. Â